Effects of Home Task on the Academic Achievement of Students at Graduate Level - Saeed, Sidra (Journal of Applied Research and Multidisciplinary Studies, 2021)
The current aims to examine the impact of home tasks on the academic achievements of students at graduation level. The main objective of the research was to find out the effects of home task descriptive feedback on students’ academic achievement, to investigate achievement of experimental group after treatment and to investigate the effect of home task on the performance of individual students. Researcher selected the population of students of Education department from Lahore College for Women University. Sample of 60 students were randomly selected. These sixty students were merged in the group of two; Experimental and Control group, on the basis of GPA. Each group was divided into fifteen students. The control group was kept under control conditions, and experimental group was given daily home task. Feedback was also given to students after each assessment. Duration of the experiment was about two months. The academic achievement of student’s was found through achievement test, data was analyzed through t-test and graph. When the treatment did provided the academic achievement of the experimental group was not increased. So, it can be concluded that home task affects negatively on the academic achievement of the students at graduation level.